Forecasting Stock Prices on the Basis of Technical Analysis in the Industrial Sectors of the UK Stock Market - Md Aminur Rahman (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to evaluate, critically and rigorously the weak-form market efficiency and forecasting power of technical analysis in different industries in the London Stock Exchange. Weekly data were collected from the FTSE-all share index, FTSE-350 general industrial index and twenty companies of four different industries, for the period between 1997 and 2017. Bai-Perron’s multiple breaks test was applied to diagnose plain data period for the purpose of forecasting. The statistical inference was made from the application of the runs test, variance ratio tests, Ljung-Box’s test and ADF-unit root test that the market is not weak-form efficient and stock prices are predictable. This study extends the current literature by considering the existence of weak-form inefficiency in different industrial sectors. The findings do not support for weak-form efficiency over the periods tested from the application of the ARIMA and GARCH (1, 1) models and double and triple exponential smoothing techniques